2022
DOI: 10.3390/molecules27123700
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Beef Burgers Formulated with Fat Substitute in a Form of Freeze-Dried Hydrogel Enriched with Açai Oil

Abstract: The growing number of people at high risk of cardiovascular disease development contributed to both changes in diets by consumers and the reformulation of food products by food producers. Cardiovascular diseases are caused by the i.a. consumption of meat that contains animal fat rich in saturated fatty acids (SFA). The use of fat substitutes in meat seems to be a promising tool for the reduction of cardiovascular disease occurrence. In the presented study, beef fat was replaced at 0 (CO), 25 (S-25%), 50 (S-50%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…During the course of 10 days of storage, the impact of In terms of color, flavor, and juiciness, the sensory evaluation of the acceptability of fat-substituted burger treatments with dry hydrogel enhanced with açai oil revealed no differences (p > 0.05). The control variant has high ratings in the analyses of appearance, color, flavor, taste, juiciness, texture, and overall acceptability, which supports the significance of the type of fat in a burger and highlights how difficult it is to fully satisfy consumer demands by using a fat replacement in place of animal fat [46]. According to Sayas-Barberá, et al [5], a new substance made from date palm coproducts (pits) was procured and tried as a burger preservative.…”
Section: Sensory Evaluationmentioning
confidence: 67%
“…During the course of 10 days of storage, the impact of In terms of color, flavor, and juiciness, the sensory evaluation of the acceptability of fat-substituted burger treatments with dry hydrogel enhanced with açai oil revealed no differences (p > 0.05). The control variant has high ratings in the analyses of appearance, color, flavor, taste, juiciness, texture, and overall acceptability, which supports the significance of the type of fat in a burger and highlights how difficult it is to fully satisfy consumer demands by using a fat replacement in place of animal fat [46]. According to Sayas-Barberá, et al [5], a new substance made from date palm coproducts (pits) was procured and tried as a burger preservative.…”
Section: Sensory Evaluationmentioning
confidence: 67%
“…There was no statistically significant difference between the samples in terms of diameter reduction (p>0.05). Hanula et al ( 27 ) reported that the highest cooking loss was in the control group. The reason for our opposite result is that the hydrogel used is lyophilized and has a low moisture content, so the loss is lower and at the same time the moisture is retained in the samples with substituted fat content.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, it was noted that the interaction between protein and emulsion was significant in the firmness of the HPP + SVCOOK sensory profile. Hanula et al [ 52 ] mentioned significant differences in the trained panel sensory analysis of reformulated beef patties (hydrogel enriched with acai oil). At the same time, Poyato et al [ 23 ] reported no significant difference in the sensory profile of reformulated pork-beef patties with carrageenan based gelled emulsion.…”
Section: Resultsmentioning
confidence: 99%